2014
DOI: 10.1517/14712598.2015.987121
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy against sarcomas

Abstract: Preclinical findings and initial clinical reports showed the potentialities and drawbacks of different adoptive immunotherapy strategies. The expansion of tumor infiltrating lymphocytes is difficult to be reproduced outside melanoma. Genetically redirected T cells appear to be a promising option and initial reports are encouraging against patients with sarcomas. Adoptive immunotherapy with MHC-unrestricted effectors such as NK, CIK or γδ T cells has recently shown great preclinical potential in sarcoma setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…The clinical translation of adoptive immunotherapy with CIK cells as treatment for patients with solid tumors is currently the object of clinical trials and their number has increased in recent years [ 1 ]. They can be classically expanded starting from peripheral blood mononuclear cells (PBMCs) [ 2 , 3 ] but may also be generated from bone marrow (BM) or umbilical cord blood precursors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical translation of adoptive immunotherapy with CIK cells as treatment for patients with solid tumors is currently the object of clinical trials and their number has increased in recent years [ 1 ]. They can be classically expanded starting from peripheral blood mononuclear cells (PBMCs) [ 2 , 3 ] but may also be generated from bone marrow (BM) or umbilical cord blood precursors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical application of T cell therapy for osteosarcoma faces several obstacles before it can be introduced into clinical practice. These include: (1) required production with stringent GMP (good manufacturing practice) procedures in dedicated facilities; (2) necessity of lymphodepleting preparative treatment; and (3) advocate combination of different immunotherapy approaches and integration with conventional treatments ( 64 ).…”
Section: Adoptive T Cell Transfer For Osteosarcomamentioning
confidence: 99%
“…The use of adoptive γδ T cell transfer in cancer immunotherapy is a new treatment, especially with regard to osteosarcomas. The main advantages and disadvantages of adoptive γδ T cell transfer immunotherapy are summarized below: (1) it is MHC-independent (all patients may benefit); (2) it is not affected by immune-escape MHC-downregulation; (3) it is not restricted to any precise sarcoma histotype; (4) it has high rates of ex vivo expansion with simple protocols; (5) it has limited persistence in vivo ; and (6) its recognition is limited to extracellular targets ( 64 ). Unlike αβ T cells, γδ T cells can naturally recognize tumor antigens in an MHC-independent manner without antigen processing.…”
Section: Adoptive T Cell Transfer For Osteosarcomamentioning
confidence: 99%
“…NK cells activation is dependent upon the activation of costimulatory NK cell receptors (NKR), including NKG2D, DNAX accessory molecule-1 (DNAM-1), 2B4, NTB-A, CRACC, CD2, CD59, NKp80, CD94/NKG2C, and of the natural cytotoxicity receptors (NCR: NKp30, NKp44, and NKp46) [ 46 ]. NK cells have a well-known capacity to kill a wide variety of tumors, like sarcoma and leukemia [ 47 49 ] but in ovarian cancer disease the efficacy of NK cells to kill tumor is not clear [ 1 ]. Carlsten et al have shown that NKs derived from healthy donor can recognize and kill in vitro ovarian carcinoma cells, isolated from peritoneal effusions, through the activation of DNAM-1 signaling with complementary contributions of NKG2D and NCR receptors [ 46 ].…”
Section: Hla Unrestricted Adoptive Immunotherapymentioning
confidence: 99%